Control regions for chromosome replication are conserved with respect to sequence and location among Escherichia coli strains - Frimodt-Møller, Jakob; Charbon, Godefroid; Krogfelt, Karen A.; Løbner-Olesen, Anders (Frontiers in Microbiology, 2015)
In Escherichia coli, chromosome replication is initiated from oriC by the DnaA initiator protein associated with ATP. Three non-coding regions contribute to the activity of DnaA. The datA locus is instrumental in conversion of DnaAATP to DnaAADP (DDAH; datA dependent DnaAATP hydrolysis) whereas DnaA rejuvenation sequences 1 and 2 (DARS1 and DARS2) reactivate DnaAADP to DnaAATP. The structural organization of oriC, datA, DARS1 and DARS2 were found conserved between 59 fully sequenced E. coli genomes, with differences primarily in the non-functional spacer regions between key protein binding sites. The relative distances from oriC to datA, DARS1 and DARS2, respectively, was also conserved despite of large variations in genome size, suggesting that the gene dosage of either region is important for bacterial growth. Yet all three regions could be deleted alone or in combination without loss of viability. Competition experiments during balanced growth in rich medium and during mouse colonization indicated roles of datA, DARS1 and DARS2 for bacterial fitness although the relative contribution of each region differed between growth conditions. We suggest that this fitness cost contribute to conservation of both sequence and chromosomal location for datA, DARS1 and DARS2.